Partogram and its relevance in modern obstetrics - Choudhary, Anjali; Tanwar, Meenakshi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Normal labor and childbirth is fraught with complexities. In the modern times the child birth has proven to be more challenging than ever. Partogram has proven to be a simple and useful tool in monitoring normal labor. The objective of this endeavor was to site our experiences in using partogram for ‘plotting’ labors, to assess its utility, limitations and cite controversies. Methods: Authors analyzed progress of labor plotted on partograms in parturient women to see whether their labor patterns conform to the standard partogram, and can logical conclusions be drawn from their use to decide partogram’s utility and applicability. Results: The use of partogram was not universal and its charting inadequate due to lack of motivation on part of labor room residents, busy labor rooms. When plotted meticulously they showed a wide variation, and many women did not conform to the rates of dilatation of the graph. The use of partogram did not alter the rate of cesarean section for non-progressive labors with use and non-use of partogram. Conclusions: Philpott’s partogram is a very visual and useful tool to monitor labours and detect labour abnormalities timely. Although it has served as a labour management tool across the labour rooms its use is not universal. There is a plethora of conflicting opinions regarding its utility in modern obstetrics today, ranging from a complete faith in the tool to finding it obsolete and in need of a revision to calling it a medicalization of a natural process.